EFFECT OF POSITION AND DIAMETER SIZE OF BURNER NOZZLE TIP ON COMBUSTION PHENOMENON AT PRIMARY REFORMER USING COMPUTATIONAL FLUID DYNAMICS SIMULATION (CFD) - Arind Pradibta, Tatang
Primary reformer has a very vital role in the production process of ammonia and urea plants. Uneven heat distribution phenomenon often occurs on the catalyst tube in the top-fired primary reformer unit. Catalyst tube leaks often occur in systems that have experienced excess heat due to uneven heat distribution, causing the ammonia and urea plants to be completely shut down and incurring economic losses. Many factors can trigger the occurrence of uneven heat distribution. The most dominant is the shape of the flame. The slanted shape of the flame causes the tip of the flame to touch the catalyst tube or so-called flame impingement. The shape of the flame itself is greatly influenced by the configuration of burner nozzle tip. This study aims to analyze the effect of position and diameter size of burner nozzle tip on the combustion phenomenon in primary reformer unit PT Pupuk Kujang 1B. Effects of position and size of diameter of the burner nozzle tip are analyzed by simulating the mass balance and heat balance simultaneously using Computational Fluid Dynamics (CFD) simulation method. The evaluation show that fuel gas flowing in the existing burner nozzle tip has very high linear velocity up to >300 m/s and causes poor internal circulation and uneven heat distribution. Therefore, it is necessary to modify the burner by improving configuration and increasing the size of the burner nozzle tip. The burner configuration proposed in this study is a burner which all nozzle tips are symmetrically positioned in the center area and each nozzle tip has size of 12 mm. The proposed burner produces a straight hot gas flow pattern and good heat distribution based on the simulation.